2012
DOI: 10.1007/s10926-012-9371-3
|View full text |Cite
|
Sign up to set email alerts
|

Policy and Practice of Work Ability: A Negotiation of Responsibility in Organizing Return to Work

Abstract: PurposeIn welfare policy and practical work it is unclear what the concept of work ability involves and assessments may be different among involved actors, partly due to a lack of theoretical research in relation to regulations and practice. Based on theoretical and legal aspects of work ability the aim of the study is to analyze stakeholders" perspectives on work ability in local practice by studying multi-stakeholder meetings. MethodsThe material comprises nine digitally recorded multi-stakeholder meetings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 21 publications
5
41
0
3
Order By: Relevance
“…This tension between social responsibility and economic interests has been observed in previous research [12,19,[38][39][40][41]. One study identified how employers experienced a conflict of interest between their formal role of implementing an early-return-to-work policy and their need to consider their production demands [39].…”
Section: Employers' Economic Perspective On Return To Work In the Conmentioning
confidence: 85%
“…This tension between social responsibility and economic interests has been observed in previous research [12,19,[38][39][40][41]. One study identified how employers experienced a conflict of interest between their formal role of implementing an early-return-to-work policy and their need to consider their production demands [39].…”
Section: Employers' Economic Perspective On Return To Work In the Conmentioning
confidence: 85%
“…It entails an orientation towards disability with focus on a person's functional and activity limitations due to illness or disease [2][3][4]. From a rehabilitation perspective, the purpose is to improve an individual's work ability after injury or illness, and work ability is often described as an interaction between the person, the task and the environment [2][3][4][5][6][7][8][9][10][11]. There has been less focus on the results of work ability, i.e.…”
Section: Work Abilitymentioning
confidence: 99%
“…In a recent Swedish study, this process was characterized as a negotiation between employers, health care professionals and insurance officials, in which employers were identified as holding the "trump card". That is, if the manager said a person could not work, this person would not be returning to that workplace (Seing et al 2012). Here, it is possible to speak of a "bottom line ethics", where the priorities are set by the stakeholder that holds the power to influence the process.…”
Section: Application To the Wdp-rtw Fieldmentioning
confidence: 99%